Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1021/bi002378f
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Inhibitors of the Processing of Pretransfer RNA by the Ribonuclease P Ribozyme:  Enzyme Inhibitors Which Act by Binding to Substrate

Abstract: 2,2'-p-Phenylene bis[6-(4-methyl-1-piperazinyl)]benzimidazole, 2,2'-bis(3,5-dihydroxyphenyl)-6,6'-bis benzimidazole, and 2,2'-bis(4-hydroxyphenyl)-6,6'-bis benzimidazole are shown by UV-visible and fluorescence spectrophotometry to be strong ligands for tRNA, giving simple, hyperbolic binding isotherms with apparent dissociation constants in the micromolar range. Hydroxyl radical footprinting indicates that they may bind in the D and T loops. On the basis of this tRNA recognition as a rationale, they were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We have demonstrated that the FP/FA assay can detect small ligand binding to pre-tRNA if the interactions alter the solution structure (Figure 4). This assay is more sensitive for measuring small ligands binding to tRNA than previous methods relying on changes in the intrinsic fluorescence of modified bases on native tRNA (49) or of the compounds (24,54,55), and other spectroscopic methods such as UV-VIS and circular dichroism (24,5456). The FP/FA assay reported here using end-labeled pre-tRNA provides a general and convenient way of measuring binding and stabilization of in vitro transcribed tRNA by non-fluorescent molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the FP/FA assay can detect small ligand binding to pre-tRNA if the interactions alter the solution structure (Figure 4). This assay is more sensitive for measuring small ligands binding to tRNA than previous methods relying on changes in the intrinsic fluorescence of modified bases on native tRNA (49) or of the compounds (24,54,55), and other spectroscopic methods such as UV-VIS and circular dichroism (24,5456). The FP/FA assay reported here using end-labeled pre-tRNA provides a general and convenient way of measuring binding and stabilization of in vitro transcribed tRNA by non-fluorescent molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoglycosides are also weak non-competitive inhibitors of eukaryal RNase P ( K i = 143 μM for neomycin B to Dictyostelium discoideum RNase P) (23). A number of synthetic compounds, including bis-benzimidazoles ( IC 50 = 5–21 μM) (24), porphines and porphyrins ( K i = 1–4 μM) (25), inhibit E. coli RNase P activity mainly through binding to pre-tRNA. Spiramycin, a macrolide antibiotic, was reported to activate the steady-state turnover catalyzed by E. coli RNase P (26).…”
Section: Introductionmentioning
confidence: 99%
“…Footprinting experiments indicate that they bind in the D and T loop regions. A few of these compounds, in particular the bis(4hydroxyphenyl) derivative, were found to inhibit tRNA processing by RNase P, also at the low micromolar levels [37]. Although no patenting activity on these compounds for an RNA-binding utility has yet appeared, the compounds are [101,104,120,121].…”
Section: Other Analoguesmentioning
confidence: 99%
“…Recently, however, certain tRNAs have been found to be disrupted, some without base modiˆcation and some under in vitro conditions. [3][4][5][6][7][8][9][10][11] In other wors, not all tRNAs are rigid, and their cloverleaf shape is not always stable. The study of such destabilized or unstable tRNAs should give clues about the ways in which tRNA molecules are stabilized and also about the origin of tRNA molecules.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] The change from a cloverleaf to a double-hairpin can be monitored by the reaction of ribonuclease P from Escherichia coli. [3][4][5][6][7][8][9][10] Ribonuclease P also has been found in all species examined. The enzyme catalyzes the 5?-processing reaction of tRNA precursors to produce a mature 5?-end in tRNA molecules.…”
mentioning
confidence: 99%